The performance of public debt since the Asian crisis: the comparison of Indonesia and Malaysia - Emirullah, Chandra (2011)
More than ten years after the financial crisis has engulfed the South East Asia, the affected countries in this region such as Thailand, Indonesia and Malaysia have mostly overcome their financial problems and returned to the path of recovery and economic growth. In the sphere of public debt, however, although they have been able to reduce their debt which had soared due to the crisis, their performance is not even. Indonesia and Thailand, mostly affected by the crisis were able to reduce their public debt to GNP ratio, the most important indicator of solvency, consistently and significantly. On the other hand, Malaysia, the less affected country, has not performed as well as the two neighboring peers. This difference can potentially be explained in terms of debt management and growth performance. This paper will look at the experience of Indonesia in comparison with Malaysia. It will argue that while the two countries have shown relatively similar ability in managing the debt, the more consistent economic growth achieved by Indonesia has helped it to grow out of its debt, reducing it below the average level of the emerging countries. Also, the conservative fiscal policy adopted by Indonesia has resulted in low budget deficits contributing to its relatively low public debt ratio.